2008
DOI: 10.1007/s10096-008-0623-2
|View full text |Cite
|
Sign up to set email alerts
|

Alternaria infectoria brain abscess in a child with chronic granulomatous disease

Abstract: In the present report, we describe the first case of a phaeohyphomycotic brain abscess in a 5-year-old boy with chronic granulomatous disease (CGD) admitted to hospital with seizures. A computed tomography (CT) scan revealed a cerebral abscess and the microbiology study showed a dark, melanin-pigmented fungus, exhibiting only sterile hyphae. This fungus was identified by the amplification and sequencing of the 5.8S RNA gene and of the adjacent internal transcriber spacer domains, ITS1 and ITS2, as Alternaria i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 19 publications
0
19
1
Order By: Relevance
“…Mortality was Ͼ70%. Since that review in 2004, over 50 cases have been reported, with C. bantiana remaining the most frequently seen isolate (131,4,17,16,22,31,40,70,78,93,121,139,170,189,243,244,268,272,276,328,332,341,363,380,399,420,433,448,450,467,476,545,575,636,657,696,700,721,731,733,754,759). A new species, Fonsecaea monophora, has been reported since that time and appears to have a predilection for causing CNS disease, in contrast to its related species, F. pedrosoi (420,721,733).…”
Section: Phaeohyphomycosismentioning
confidence: 99%
“…Mortality was Ͼ70%. Since that review in 2004, over 50 cases have been reported, with C. bantiana remaining the most frequently seen isolate (131,4,17,16,22,31,40,70,78,93,121,139,170,189,243,244,268,272,276,328,332,341,363,380,399,420,433,448,450,467,476,545,575,636,657,696,700,721,731,733,754,759). A new species, Fonsecaea monophora, has been reported since that time and appears to have a predilection for causing CNS disease, in contrast to its related species, F. pedrosoi (420,721,733).…”
Section: Phaeohyphomycosismentioning
confidence: 99%
“…Another A. infectoria clinical isolate was used for determination of the polyketide synthase nucleotide sequence. The latter isolate was previously obtained by us (30) and is deposited in the CBS collection as strain CBS 122351. A. alternata was kindly provided by R. Freitas and R. M. B. Ferreira (Instituto Superior de Agronomia, Universidade de Lisboa, Lisbon, Portugal).…”
Section: Organisms and Mediamentioning
confidence: 99%
“…Clinical manifestations of the saprobic Alternaria species usually are cutaneous or subcutaneous lesions after trauma (Halaby et al 2001;Lo Cascio et al 2004) in patients under prolonged corticosteroid treatment. Other clinical entities, such as cerebral infections, sinusitis, keratitis, and allergic bronchopulmonary mycosis, are very rare (Hipolito et al 2009;Chowdhary et al 2012Chowdhary et al , 2014a. The most common etiologic agents are Alternaria alternata and Alternaria infectoria and, occasionally, Alternaria chlamydospora.…”
Section: Black Molds and Yeasts Pathogenic To Humansmentioning
confidence: 99%